Pengaruh Sales Growth, Inventory Intensity, dan Capital Intensity terhadap Agresivitas Pajak pada Perusahaan JII - Setiawati, Putri; Sunarmi, Sunarmi (Journal of Business and Economics Research (JBE), 2024)
This study aims to determine the effect of sales growth, inventory intensity, and capital intensity on tax aggressiveness in companies listed on the Jakarta Islamic Index (JII) for the 2019-2023 period. The method used in this research is quantitative research method. The sampling technique used purposive sampling, where the population in this study amounted to 150 company data. Based on the sample criteria, the number of research samples obtained was 60 company data. The type of data in this study uses secondary data which is tested using SPSS v.25 with multiple linear regression analysis techniques. The results prove that partially sales growth has no effect on tax aggressiveness. This is evidenced by the significance value obtained of 0,468 > 0,05, which means that H1 is rejected. Inventory intensity has no effect on tax aggressiveness. This is evidenced by the significance value obtained of 0,207 > 0,05, which means H2 is rejected. Capital intensity has no effect on tax aggressiveness. This is evidenced by the significance value obtained of 0,137 > 0,05, meaning that H3 is rejected. Simultaneously, it shows that sales growth, inventory intensity, and capital intensity have no effect on tax aggressiveness. This is evidenced by the significance value of 0,236 which means greater than 0,05.